2013
DOI: 10.1111/joes.12029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on the Impact of Tariff Reductions on Employment in Developing Countries: A Systematic Review

Abstract: This paper analyses the evidence on the impact of tariff reductions on employment in developing countries. We carry out a systematic review of the existing empirical literature, and include both, ex post econometric evidence and ex ante Computable General Equilibrium (CGE) simulation studies. The synthesis of results suggests that the effects of tariff reductions on employment are country and trade policy specific. When looking across higher quality econometric studies that control for the endogeneity of tarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Our results are consistent with this finding, in so far as trade liberalization increases the level of output. In their survey of the evidence on the empirical effects of tariff reductions on employment (in developing countries), Cirera et al (2013) found that, when openness indicators (a share of exports, imports or both, over GDP) are used as the trade policy proxy, more openness is associated with higher employment. Fig.…”
Section: Effects Of a Unilateral Tariff Reductionmentioning
confidence: 98%
“…Our results are consistent with this finding, in so far as trade liberalization increases the level of output. In their survey of the evidence on the empirical effects of tariff reductions on employment (in developing countries), Cirera et al (2013) found that, when openness indicators (a share of exports, imports or both, over GDP) are used as the trade policy proxy, more openness is associated with higher employment. Fig.…”
Section: Effects Of a Unilateral Tariff Reductionmentioning
confidence: 98%
“…Studies that looked at impact of programmes that we did not consider a public intervention targeted exclusively to SMEs were dropped (Bah et al, 2011). Studies that looked at the impact of export zones, such as Cirera et al (2011) and Cirera et al (2013), were dropped. Finally, studies (RCTs) that did not clearly test a public policy and that was conducted with rural firms only such as Giné and Mansuri (2011) were not included in the review.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Our results are consistent with this finding, in so far as trade liberalization increases the level of output. In their survey of the evidence on the empirical effects of tariff reductions on employment (in developing countries), Cirera et al (2013) found that, when openness indicators (a share of exports, imports or both, over GDP) are used as the trade policy proxy, more openness is associated with higher employment. Figure 1(i) indicates that the value of trade liberalization is negative for the home country.…”
Section: Figure 1 Effects Of a Unilateral Domestic Tariff Reductionmentioning
confidence: 99%